HOW CAN DRAMA COACH ENHANCE STUDENTS’ ENGLISH SELF-ESTEEM AND SPEAKING PERFORMANCE? - Suramto; Episiasi; Yentri Anggeraini (Language and Education Journal, 2024)
The study aimed to determine if students' self-esteem and speaking proficiency significantly changed after receiving instruction from a drama coach. The 60 general conversation students, who ranged in age from 15 to 17, were the subjects of the study. In this study, a quasi-experimental design was used. A speaking achievement test and a self-esteem questionnaire were distributed to gather data. Three raters conducted interviews to collect data on speaking scores. Based on the findings, students who received drama coach treatment had higher mean scores in speaking achievement (81.46) and self-esteem (80.57). Additionally, the drama coach influenced students' self-esteem (29.7%) and speaking proficiency (58.8%). The remaining 11.5% may be influenced by additional factors not included in the research. The drama coach's role improved the teenagers' ability to speak English.